Peningkatan Efektivitas Kerja melalui Perbaikan Pelatihan, Penjaminan Mutu, Kompetensi Akademik dan Efikasi Diri dalam Organisasi Pendidikan - Santa Manurung; Rais Hidayat; Yuyun Elizabeth Patras; Rhini Fatmasari (MANAGERIA: Jurnal Manajemen Pendidikan Islam, 2018)
The research is conducted at the Health Polytechnic of the Ministry of Health of DKI Jakarta III to obtain information on the effect of training, quality assurance, pedagogic competence, and self-efficacy towards lecturers’ job effectiveness. The research used 60 out of 145 lecturers as the population selected using simple random sampling. The research is conducted by using a method of causal with path analysis. The result of the research showed that: (1). there is a direct positive effect of training on lecturers’ job effectiveness; (2) there is a direct effect quality assurance on lecturers’ job effectiveness; (3) there is a direct effect of pedagogic competence on lecturers’ job effectiveness; (4) there is a direct effect of self-efficacy on lecturers’ job effectiveness. Therefore, job effectiveness of Health Polytechnic lecturers of the Ministry of Health Jakarta III can be enhanced by carrying out training, quality assurance, pedagogic competence, and self-efficacy.